Study on Energy Density Distribution and Mass Fractal of Deep Saturated Coal Samples under Uniaxial Stepwise High Stressed Loading and Unloading Path. (16th September 2022) - Chen, Xiaoyu; Yao, Qiangling; Shan, Changhao; Yu, Liqiang; Chen, Liang; Xu, Qiang; Xia, Ze; Zhu, Liu
Abstract : The geostress in deep coal roadway is high and affected by mining frequently; under the influence of water-rock interaction, the bearing capacity of coal continues to deteriorate. Based on the characteristics of short water absorption process and low moisture content of deep coal samples in this experiment, the threshold range of quantitative division of water absorption stage of coal samples is given, and the structural characteristics of deep coal samples that are more susceptible to cracks are analyzed. The actual loading process is simulated through uniaxial stepwise high stressed loading and unloading experiments, the gradual development of cracks was the root cause of instability of coal, and saturated water mainly aggravates the instability process through these cracks; the stepwise high stressed loading and unloading path makes cracks more likely to occur in the sample. After each level of loading and unloading, the average stiffness is approximately linear trend degradation. By calculating the energy density of deep coal samples in each stage before the peak, the change of energy density indexes between saturated and dried samples is different from relative shallow samples, and the energy density indexes do not decrease but increases instead. However, the proportion of each energy is generally positive and inverted "U"-type distribution. The change trend of plastic energy in proportion to dissipation energy can be used as the judgment feature of coal sample instability. The instability of deep coal samples is mainly caused by the gradual dissipation of plastic energy to generate cracks and divided into fragments with large and long edge, resulting in low mass fractal dimension. In engineering practice, the loading times should be reduced and the suitable pressure grouting should be conducted timely to delay the deterioration process of crack development in deep water-bearing coal under high stress disturbance.